A Cross-National Analysis of the (Re)actualization of Work Experience Placement as a Career Education Activity in Sweden and Denmark - Mahtab Eshaghbeigi-Hosseini (Nordic Journal of Transitions, Careers and Guidance)
This article explores policy arguments for the re-actualization of work experience placement (WEP) as a career education and guidance (CEG) activity in Sweden and Denmark through analysis of problematizations and assumptions that underpin its re-actualization as a CEG activity in the two countries. The exploration focuses on core policy documents that widened the right to WEP in Denmark in 2017/18 and reintroduced mandatory WEP in Sweden in 2018. The results show that WEP was actualized by a problematization of the decline in applications for upper secondary vocational education (VET) and accompanying concerns regarding the supply of competences needed by the labour market. The decline was assumed to be due to young people’s lack of interest in VET. This, in turn, was attributed to their lack of knowledge and contact with the world of work and insufficient preparation in compulsory schools to enable them to make informed educational and vocational choices. The ability of the policies that address WEP to reach the goal of increasing young people’s interest in VET is questioned and social justice concerns are raised. It is argued that isolated WEP events do not necessarily increase young people’s interest in, or knowledge of, VET. Instead, WEP must be embedded in a systematic and coherent CEG program that can support expansion of the space of valued occupational options. Abstrakt Denne artikel undersøger policyargumenter for re-aktualisering af erhverspraktik (WEP) som en karrierelæringsaktivitet i Sverige og Danmark gennem en analyse af hvilke problematiseringer der ligger til grund for denne re-aktualisering af erhvervspraktik som karrierelæringsaktivitet. Udforskningen fokuserer på de policydokumenter, der udvidede retten til erhvervspraktik i Danmark i 2017/18 og genindførte obligatorisk praktik i Sverige i 2018. Resultaterne viser, at erhvervspraktik blev aktualiseret ved en problematisering af nedgangen i ansøgninger til de gymnasiale erhvervsuddannelser (EUD), og medfølgende bekymringer vedrørende udbuddet af kompetencer, som arbejdsmarkedet har brug for. Nedgangen blev antaget at skyldes unges manglende interesse for EUD. Dette forklares med unges manglende viden og kontakt til arbejdslivet og utilstrækkelige forberedelser i grundskolerne i at understøtte dem i at træffe informerede uddannelses- og erhvervsvalg. Artiklen sættes spørgsmålstegn ved WEP-politikkernes evne til at nå målet om at øge unges interesse for EUD og mulige udfordringer i relation til social retfærdighed rejses. Det hævdes, at erhvervspraktik alene ikke nødvendigvis øger unges interesse for eller viden om EUD. I stedet skal WEP placeres i et systematisk og sammenhængende karrierelæringsprogram som kan understøtte en udvidelse af hvilke erhverv som anses for værdifulde. Nøgleord: Karrierelæring; karrierevejledning; erhvervspraktik; uddannelsesog erhvervsvalg; social retfærdighed